IDENTIFIKASI LEVEL KINERJA NOVICE MELALUI KEMAMPUAN BERFIKIR KRITIS SISWA (INTERPRETASI, ANALISIS) - Indah Rahayu Panglipur; Eric Dwi Putra (Universitas Insan Budi Utomo, 2019)
The aspect that has an important role in education is learning, so it needs to be developed in order to explore the potential in students so that it is expected to create quality graduates from the teaching process that has been implemented by the teacher. Every student can be trained for their critical abilities and always be improved. This type of research used in this study is a qualitative study using a description approach. Subjects were taken based on daily test scores that have been documented by the mathematics teacher. Data collection techniques using tests and interviews. Based on the result of this study known that the level of novice performance through the ability to think critically that the aspect of student interpretation can not present problems according to questions in the form of mathematical language clearly and in the analysis aspect students do not write the information contained in the questions and students can write the concept however is still wrong or incompatible.